Standard magnitude sequences in the Harvard standard regions at -45° declination - Cousins, Alan William James (Department of Astronomy, 2016)
Accurate stellar magnitudes on a uniform system are necessary for astronomical research. The North Polar Sequence, which defines the International System, is not accessible to southern observers so it has been necessary to establish magnitude sequences in the Southern Hemisphere. A number of observing programmes to establish such sequences in the nine Harvard Standard E Regions have been carried out using modern methods. Two of these programmes employing the Fabry method and a photoelectric photometer, respectively, are described in some detail. A special series of observations was made to ensure that the nine E regions have the same zero point. Accurate photographic and photovisual magnitudes were obtained for about 270 of the brighter stars. In a concluding section, modern material is collected and combined to give accurate magnitudes, the majority in two colours, for 640 stars, and approximate data for many more. The data have been examined and found to be free from systematic errors between magnitudes 3.0 and 10.0. The reductions to the adopted colour systems are also satisfactory. The most urgent need at present is for more observations of the fainter stars.